Evidence for geochemical control of iron by humic substances in seawater - Luis M. Laglera; Constant M. G. van den Berg (Limnology and Oceanography, 2009)
A new method, based on the direct detection of iron‐humic substance (HS) species by cathodic stripping voltammetry (CSV), is used to determine the iron binding capacity and complex stability of fulvic acid (FA), humic acid (HA), and the natural HS in the seawater. The FA binds 16.7 ± 2.0 nmol iron (Fe) (mg FA)−1, whereas the HA and the marine HS bind 32 ± 2.2 nmol Fe (mg FA) ‐1 . The complex stabilities are (log K’ Fe’HS values) 10.6 for FA and 11.1 for HA and coastal HS. Measurements of coastal waters (Irish Sea) show that the HS occur in a widespread fashion, the HS concentration decreasing with increasing salinity and occurring at levels of 400 (at salinity 30) to 70 (at salinity 34) µg L −1 . A sample from the deep Pacific was found to contain 36 µg HS L −1 , amounting to 4% of the dissolved organic matter. Comparative measurement of the total iron complexing capacity by CSV with competitive ligand exchange showed that the natural HS can account for the entire ligand concentration in the shallow coastal and deep ocean waters tested. Measurements of the iron solubility showed that FA added to seawater and the HS in coastal waters maintain iron in solution at a level just below the iron binding capacity. The preliminary data for the open ocean indicate that the same may be true for HS in deep ocean waters. The data are consistent with a mechanism by which iron is transported from land to sea, associated with land‐derived HS.